"Sculptors and their Drawings : Selections from the Hirshhorn Museum Collection". - Lyndon Baines Johnson Library (Washington : Hirshhorn Museum and Sculpture Garden, 1974)
Rodin, Auguste ; Giacometti, Alberto ; Hepworth, Barbara ; Moore, Henry ; Smith, David ; Calder, Alexander ; Ernst, Max ; Matisse, Henri ; Nadelman, Ele ; Manzu, Giacomo
"Sculptors and their Drawings : Selections from the Hirshhorn Museum Collection", Lyndon Baines Johnson Library, Oct. 4, 1974 - Jan. 5, 1975
Engels
boek